2018
DOI: 10.2737/nrs-rb-118
|View full text |Cite
|
Sign up to set email alerts
|

Ohio Forests 2016

Abstract: This report constitutes the third full report of annualized inventory on Ohio forest land and summarizes field data collected from 2011 through 2016. Ohio has 8.0 million acres of forest land containing 103 tree species and 50 forest types. Net cubic-foot and sawtimber volumes continued to increase, as did the area occupied by large diameter stands. Growing-stock volume remained stable overall, though it decreased 3 percent on private land since 2006. The net-growth-to-harvest-removals ratio dropped from 2.3:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Based on landscape fragmentation status, we see Ohio as a strong candidate for broad application of low-severity forestry methods like CTNF. Riitters 96 singled out the Ohio River Valley as one of the two most severe hotspots of forest edge and patch fragmentation in the country and Albright et al 97 reported that from 1990 to 2010, Ohio’s core forests dropped from 32% to 23% statewide. While Ohio forest fragmentation is often attributed to roadways and the residential development from population sprawl, 71 high-severity timber practices may further degrade this fragile landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Based on landscape fragmentation status, we see Ohio as a strong candidate for broad application of low-severity forestry methods like CTNF. Riitters 96 singled out the Ohio River Valley as one of the two most severe hotspots of forest edge and patch fragmentation in the country and Albright et al 97 reported that from 1990 to 2010, Ohio’s core forests dropped from 32% to 23% statewide. While Ohio forest fragmentation is often attributed to roadways and the residential development from population sprawl, 71 high-severity timber practices may further degrade this fragile landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Following the seasonal changes in local climate, the annual forest growth in Ohio is divided into leaf-on seasons and leaf-off seasons. The considerable core forests deep inside the Ohio rolling mountains provide critical habitats for various wildlife species [38], for instance, songbirds, reptilians, and insects.…”
Section: Study Areamentioning
confidence: 99%